Introduction to addiction psychiatry - Chambers, R. Andrew (Cambridge University Press, 2025)
This essential, concept-oriented book provides a highly integrative and translational approach to addiction, offering a deep understanding of the condition and its close biological-causal-developmental linkage with mental illness. The book explains addiction around five fundamental components that define disease: 1) Population Impact; 2) Symptom Sets; 3) Disorder of Anatomical Structure and Function; 4) Biological Risk Amplification; and 5) Diagnosis and Treatment. Key evidence and concepts from basic neuroscience are translated to epidemiological, clinical-observational, and treatment levels. The book discusses the broad reach and potent clinical capabilities of addiction psychiatry teams using integrative diagnostics and multi-dimensional treatment plans for patients across the entire addiction-mental illness spectrum. It introduces science-based psychotherapies, therapeutic experiences, medication and neurostimulatory treatments used by addiction psychiatrists in different settings to advance patients through all stages of recovery. An illustrated foundation for advanced undergraduates, physicians, allied clinicians, and scientists entering brain-behavioural health fields.